2019
DOI: 10.1002/ppap.201900051
|View full text |Cite
|
Sign up to set email alerts
|

Atomic layer etching of SiO2 with Ar and CHF3 plasmas: A self‐limiting process for aspect ratio independent etching

Abstract: With ever increasing demands on device patterning to achieve smaller critical dimensions, the need for precise, controllable atomic layer etching (ALE) is steadily increasing. In this work, a cyclical fluorocarbon/argon plasma is successfully used for patterning silicon oxide by ALE in a conventional inductively coupled plasma tool. The impact of plasma parameters and substrate electrode temperature on the etch performance is established. We achieve the self‐limiting behavior of the etch process by modulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
1
28
0
Order By: Relevance
“…3. As noticed in our previous work, 13 the substrate temperature has a non-negligible impact on the ALE performances, since it strongly affects the sticking coefficient of the deposited FC polymer and therefore the overall ALE process. 16 In addition, the temperature also has a significant effect on the chemical etching caused by fluorine in the chamber.…”
Section: A Effect Of the Substrate Temperature On Ale Mechanismmentioning
confidence: 53%
See 4 more Smart Citations
“…3. As noticed in our previous work, 13 the substrate temperature has a non-negligible impact on the ALE performances, since it strongly affects the sticking coefficient of the deposited FC polymer and therefore the overall ALE process. 16 In addition, the temperature also has a significant effect on the chemical etching caused by fluorine in the chamber.…”
Section: A Effect Of the Substrate Temperature On Ale Mechanismmentioning
confidence: 53%
“…17 chemical reaction between SiO and FC results in a higher etch rate, but at the expense of the film integrity and etch selectivity for SiO 2 over other materials. [18][19][20] However, while we demonstrated that ALE at T = −10°C ensures self-limiting behavior and aspect-ratio independent etching, 13,21,22 to date, no study has been reported on the temperature effect on the ALE patterning of silicon oxide.…”
Section: A Effect Of the Substrate Temperature On Ale Mechanismmentioning
confidence: 75%
See 3 more Smart Citations